Removal of ammonium from aqueous solutions using alkali-modified biochars. Issue 1 (1st October 2016) - Liu, Zhigang; Xue, Yingwen; Gao, Fei; Cheng, Xiaoru; Yang, Kai
Abstract: Biochars converted from agricultural residuals can effectively remove ammonium from water. This work further improved the sorption ability of biochars to aqueous ammonium through alkali modification. Three modified biochars were prepared from agricultural residuals pre-treated with NaOH solution through low-temperature (300 °C) slow pyrolysis. The modified biochars effectively removed ammonium ions from water under various conditions with relatively fast adsorption kinetics (reached equilibrium within 10 h) and extremely high adsorption capacity (>200 mg/g). The Langmuir maximum capacity of the three modified biochars were between 313.9 and 518.9 mg/g, higher than many other ammonium adsorbents. Although the sorption of ammonium onto the modified biochar was affected by pH and temperature, it was high under all of the tested conditions. Findings from this work indicated that alkali-modified biochars can be used as an alternative adsorbent for the removal of ammonium from wastewater.